Misrecognized materialists : social movements in Canadian constitutional politics - James, Matt, 1965- (UBC Press, 2006)
Canada's history of intense constitutional debate is often depicted as a source of national embarrassment -- a diversion from more sensible endeavours. Misrecognized Materialists tells a different story. Beginning with the Rowell-Sirois hearings of the Great Depression and concluding with the national unity wars of the late 1980s and early 1990s, Matt James details how groups representing marginalized constituencies -- women, working-class people, and ethnocultural minorities -- were able to use the Canadian constitutional arena to pursue traditionally neglected aspirations and concerns. With concrete illustrations and case studies, James questions the common tendency to interpret recognition struggles as departures from traditional "materialist" priorities such as economic security and personal safety. Ultimately, he argues that such materialist priorities were and are, in fact, at the heart of the fight for recognition for many marginalized groups. A book with provocative implications for students and scholars of social movements and identity politics, Misrecognized Materialists offers a fresh and important perspective on Canada's constitutional struggles over civic symbolism and identity.